IDENTIFIKASI DIMENSI SKILL LULUSAN PENDIDIKAN VOKASI DENGAN KEBUTUHAN KETERAMPILAN KERJA DI INDUSTRI - ISNANDAR, ISNANDAR; MULIADI, MULIADI; NURMALASARI, RIANA; MAULA, PUTRINDA INAYATUL (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Economic development strategies often target high-skill, high-wage industries and jobs. However, the relationship between skills and wages is not always balanced. The skills needed by workers in industry today include dimensions of skills for the benefit of the industry in the future. The aim of this research is to analyze the dimensions of workers' current skills related to the competencies they possess and the position they occupy so that the relationship between the two is known. This research was conducted by doctoral education students majoring in vocational education. The method used is quantitative to understand the dimensions of skills possessed by vocational education graduates who are currently working in industry. The results of this research show that all of these competency dimensions are very much needed because all workers, managers and positions within the company agree 66.7% that these dimensions are very important and needed in the future. Dimensions of competency in individuals such as task skills, task management skills, contingency management skills, job role environment skills and transfer skills are very important for employees and workers in industry to have. ABSTRAKStrategi pembangunan ekonomi seringkali menyasar industri dan pekerjaan yang berketerampilan dan berupah tinggi. Namun hubungan antara keterampilan dan upah tidak selalu seimbang. Keterampilan yang dibutuhkan oleh pekerja di industri saat ini mencakup dimensi keterampilan untuk kepentingan industri dimasa depan. Tujuan penelitian ini adalah menganalisis dimensi keterampilan pekerja saat yang berkaitan dengan kompetensi yang dimiliki dan jabatan yang diduduki sehinga diketahui keterkaitan antara keduanya. Penelitian ini dilakukan oleh mahasiswa pendidikan doktor jurusan pendidikan vokasi. Metode yang digunakan adalah kuantitatif untuk memahami dimensi skill yang dimiliki lulusan pendidikan kejuruan yag sedang bekerja di industri. Hasil penelitian ini menunjukkan bahwa semua dimensi kompetensi tersebut sangat dibutuhkan karena semua pekerja dan pegawai manager maupun posisi jabatan dalam perusahaan setuju 66,7% bahwa dimensi tersebut sangat penting dan dibutuhkan dimasa depan. Dimensi kompetensi dalam individu seperti task-skills, task management skills, contingency management skills, job role environment skills dan transfer skill sangat penting untuk dimiliki oleh pegawai maupun karyawan di industri.